The Textual Environment of George Meredith - Frankel, Nicholas (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractMeredith’s poetics, explicitly articulated and theorized in his poem “The Woods of Westermain,” are diametrically opposed to those of New Criticism. Always conscious of its own incompleteness, Meredith’s poetry calls out its reader as an active co-producer of meaning. For this reason, like Robert Browning’s, Meredith’s work has been haunted by critical accusations of obscurity and incoherence since its earliest publication. This essay argues that Meredith’s poetry dissolves the customary imagined boundaries between poem, text and reader – between perceiving subject and perceived object – in order to produce an expanded sense of consciousness that can broadly be termed “environmental.” Such a poetics, moreover, constitutes an integral part of a broader environmental philosophy running through Meredith’s poetry. This philosophy challenges limited concepts of “text” that often govern scholarship today. In Meredith’s hands, “text” includes not merely the poem on the page but the larger situation within which the poem comes into being – the reading scene, the book of poems, and above all the graphic media (paper, ink, typeface, illustrations, etc) that constitute the poem’s literal environment.